2020
DOI: 10.1111/and.13583
|View full text |Cite
|
Sign up to set email alerts
|

Effect of venous reflux time on testosterone and semen parameters of infertile males after microscopic varicocelectomy

Abstract: This study aimed to search whether there is a link between reflux flow and hormonal profile. Data of 250 patients were retrospectively investigated. Pre‐operative and 6th month semen analyses of these patients' results were compared with pre‐operative and post‐operative 6th month serum levels of testosterone. Based on the venous flow on pre‐operative Doppler ultrasonography, patients were divided into two groups. Patients with a venous flow ≤4 s were assigned to Group 1 and those with a venous flow >4 s to Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…Receiver operating characteristic curve (ROC) prediction curve showed that LTSWE in VC group had predictive value for abnormal T: when the LTSWE ≥ 5.310 Kpa, T was more likely to be abnormal, with a sensitivity of 65% and a specificity of 74.03% ( p < 0.05). Similar to our study, Senturk et al studied the effect of continuous spermatic vein reflux on the changes of semen parameters in VC‐induced infertility patients after microsurgery, they found that T was more likely to increase when the continuous regurgitation of the spermatic vein reached 4s before surgery, the sensitivity and specificity were 79.8% and 72.8% respectively (Senturk et al, 2020). The duration of continuous spermatic vein reflux was also part of the VC ultrasound grading in our study, which is widely used in clinical practice.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Receiver operating characteristic curve (ROC) prediction curve showed that LTSWE in VC group had predictive value for abnormal T: when the LTSWE ≥ 5.310 Kpa, T was more likely to be abnormal, with a sensitivity of 65% and a specificity of 74.03% ( p < 0.05). Similar to our study, Senturk et al studied the effect of continuous spermatic vein reflux on the changes of semen parameters in VC‐induced infertility patients after microsurgery, they found that T was more likely to increase when the continuous regurgitation of the spermatic vein reached 4s before surgery, the sensitivity and specificity were 79.8% and 72.8% respectively (Senturk et al, 2020). The duration of continuous spermatic vein reflux was also part of the VC ultrasound grading in our study, which is widely used in clinical practice.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to our study, Senturk et al studied the effect of continuous spermatic vein reflux on the changes of semen parameters in VCinduced infertility patients after microsurgery, they found that T was more likely to increase when the continuous regurgitation of the spermatic vein reached 4s before surgery, the sensitivity and specificity were 79.8% and 72.8% respectively (Senturk et al, 2020).…”
Section: Testicular Shear Wave Elastic and Semen Parameterssupporting
confidence: 89%